Effects of interactive whiteboard technology on the achievement and engagement of elementary-aged students with high-functioning Autism Spectrum Disorder in the content of reading - Stanley, Nicole, author; Gloeckner, Gene, advisor; Fidler, Deborah, committee member; Folkestad, James, committee member; Wallner, Barbara, committee member (Colorado State University. Libraries, 2016)
This dissertation examined the effects of interactive whiteboards (IWB) during reading instruction on student engagement and achievement with three elementary-aged students with identified Autism Spectrum Disorder (ASD). To date, the majority of the literature references regular classroom instruction and not special populations. A quantitative-dominant mixed methods approach was implemented. It included experimental methods to collect achievement and engagement data, and a post-study interview to get a more in-depth understanding of the research. The same participants were used in both the quantitative and qualitative phases. The experimental phase consisted of two methods of delivery of the same reading intervention-traditional paper materials and on an IWB alternated in an A-B-A-B design. During the traditional delivery, students received books and corresponding worksheets in paper form. During the IWB condition, each student read the books and completed corresponding worksheets on the IWB. For the purpose of the study, data were collected on achievement and engagement of these three students. The percent of questions answered correctly answered on bi-weekly comprehension quizzes and word fluency was measured for student achievement. The frequency of joint attention (JA) behaviors was measured for student engagement. The second phase served a supporting qualitative component. At the conclusion of the experimental phase, structured interviews were conducted individually with each participant to examine the perceptions of the students on integration of the IWB into reading instruction. This study examined between and within-phase patterns of achievement and engagement for each student. It included descriptive statistics of the data, visual analysis with line graphs that displayed data phase-by-phase, and statistical analysis. In total, no noticeable differences or statistical significance was found in achievement or engagement between the two methods of intervention for the students with ASD. While a few correlations were found, they were only found in one variable in each category of achievement and engagement. All three participants did not have correlations for both of the two measurable variables for achievement. Also, all three participants did not have correlations for more than one of the four measured variables for engagement. Students expressed both positive and negative aspects of both conditions; however, a preference was given to the IWB. Suggestions for further research are incorporated as part of the study results. This dissertation may impact financial decisions related to purchasing technology for school administrators for their buildings. As demand for the use of technology in educational settings increase, along with the need for evidence-based interventions for students with ASD, administrators are faced with making decisions regarding the type of technology, the impact of technology, and the cost/benefits of particular technologies within school settings.